Altitudinal Zonation of Exomorphogenesis in Northern Tien Shan. Issue 7 (2016) - Veselova, Larysa K.; Bexeitova, Roza T.; Kassymkamova, Khaini-Kamal M.; Duisebaeva, Kulzada Zh.; Turapova, Rahat O.; Tumazhanova, Saltanat O.; Taukebaev, Omirzhan Z.
No abstract available